Senile dementia and psychiatric stigma among community health service providers and relatives of diagnosed and suspected dementia patients: a cross-sectional study - Zhang,Qiwen; Deng,Jing; Luo,Huanyue; Wang,Li (PeerJ, 2023)
Background The number of people suffering from dementia is increasing rapidly in China. Early identification, referral, and intervention for dementia patients within communities are important to public health. However, these measures could be impacted by misconceptions about dementia and associated psychiatric stigma from community health professionals and relatives of dementia patients. Methods A cross-sectional survey was conducted on 249 participants, which included community doctors, community nurses, and relatives of diagnosed and suspected dementia patients in Guiyang, China. Participants were recruited through convenient sampling. The Chinese version of Dementia Knowledge Assessment Scale (DKAS) and the Perceived Psychiatric Stigma Scale (PPSS) were used to evaluate the participants’ knowledge of dementia and dementia-related psychiatric stigma. Results A total of 249 participants completed the questionnaire. The participants had moderate overall knowledge of dementia and the associated psychiatric stigma. Participants who were ≥45 years old, had a low level of education, had a low monthly income, or gained knowledge of dementia through non-media channels had lower awareness of dementia and stronger psychiatric stigma. In the “Communication & behavior” subscale of DKAS, all participants had a low level of awareness. Relatives of diagnosed and suspected dementia patients had higher total PPSS and “Marital preclusion” subscale scores than community doctors and nurses but lower psychiatric stigma based on the PPSS “Self-deprecation” subscale score. Conclusions Despite their profession, community doctors and nurses did not show an absolute advantage over relatives of diagnosed and suspected dementia patients in the dementia knowledge, and they even showed higher psychiatric stigma in some subscales. The self-deprecation subscale is related to the identification with negative labels such as “people with a mental illness are the weak”. This study shows that reducing stigma on the “Self-deprecation” subscale should be a core component of training and educational programs targeted at improving dementia knowledge among community health service providers.
Keywords: Public health; Dementia; Suspected dementia; Health service use; Knowledge; Psychiatric stigma; Health service providers; Relatives; Community; Delayed diagnosis